2017
DOI: 10.7454/eki.v1i4.1782
|View full text |Cite
|
Sign up to set email alerts
|

Kebijakan Penetapan Tarif Seksio Sesarea Tanpa Penyulit dengan Metode Activity Based Costing Berdasarkan ICD-9CM pada Jaminan Kesehatan Nasional di Rumah Sakit XY Kabupaten Kudus Tahun 2016

Abstract: AbstrakTarif Sectio Caesarea (SC) dalam program JKN jauh berbeda dengan tarif di Rumah Sakit. Sehingga perlu dilakukan penelitian tentang kebijakan penetapan tarif seksio sesarea tanpa penyulit dengan metode activity based costing (ABC) berdasarkan ICD-9cm dalam program JKN di RS XY Kabupaten Kudus. Studi kasus ini menggunakan pendekatan kuantitatif yang didukung data kualitatif dan terbagi tiga tahap : 1). Brainstorming dan Focus Group Discussion (FGD) untuk penyusunan Clinical Pathway (CP) SC Tanpa Penyulit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This is also in line with the research conducted which examined the rates for Caesarean without complications at XY Hospital in Kudus Regency, from the results of the study it was found that there was a difference between the real costs incurred by the hospital and the standard INACBGs rates (Widjayanto & Suryawati, 2017). INACBGs rates cannot cover hospital expenses in providing Caesarean services without complications (Widjayanto & Suryawati, 2017) The concept of the Activity Based Costing (ABC) system is generally applied to increase the effectiveness and efficiency in the use of costs in various organizations, which is reflected in the creation of a cost system that refers to activities. For health organizations, this concept is very good to support the social mission they carry, because this concept will create efficiency and effectiveness in terms of cost consumption which Syntax Health Sains: Vol.…”
Section: Introductionsupporting
confidence: 81%
“…This is also in line with the research conducted which examined the rates for Caesarean without complications at XY Hospital in Kudus Regency, from the results of the study it was found that there was a difference between the real costs incurred by the hospital and the standard INACBGs rates (Widjayanto & Suryawati, 2017). INACBGs rates cannot cover hospital expenses in providing Caesarean services without complications (Widjayanto & Suryawati, 2017) The concept of the Activity Based Costing (ABC) system is generally applied to increase the effectiveness and efficiency in the use of costs in various organizations, which is reflected in the creation of a cost system that refers to activities. For health organizations, this concept is very good to support the social mission they carry, because this concept will create efficiency and effectiveness in terms of cost consumption which Syntax Health Sains: Vol.…”
Section: Introductionsupporting
confidence: 81%
“…In other study 11 , higher coverage of first-and second-class patients were able to cover third-class patient cost through activity-driven cost control. Factors affecting high treatment cost including length of treatment 12 , severity and accompanying diagnoses 13 , medical services reimbursement 14 , patient treatment class 15 , inappropriate insurance coding 16 , completeness of patient medical record 13 . In light of these factors, cost control could be applied through reduction of treatment length 15,17 , optimization of staff to patient ratio 16 , privately-funded VIP healthcare services 18 , and conducting medical treatments in accordance to clinical pathway 19 may allow hospitals to recover deficits caused by national healthcare system.…”
Section: Resultsmentioning
confidence: 99%
“…Activities in clinical pathways are cost objects used as the basis for calculating unit costs (Hidhayanto, 2009). The calculation of unit costs based on CP activities (CP costing) is an effort to control quality (Widjayanto et al, 2017). CP costing calculates the cost of each activity and resource.…”
Section: Introductionmentioning
confidence: 99%
“…The results of activity cost analysis using the ABC method can be used to redesign CP. ABC is a cost analysis method that supports cost control efforts (Cannavacciuolo et al, 2015;González et al, 2005) (Widjayanto et al, 2017). The ABC method increases resource management, promotes improved performance, identifies non-value added, motivates cost reduction, optimizes the use of resources, and improves organizational efficiency (Aurelia & Pujiyanti, 2017;Mehtap Aldogan et al, 2014;Surendra P. Agrawal et al, 1998) Non-value-added activities do not provide value to the customer or can be said as an activity that the customer does not require.…”
Section: Introductionmentioning
confidence: 99%